Anatomical and functional characteristics of the pelvic floor in nulliparous women submitted to three-dimensional endovaginal ultrasonography: case control study and evaluation of interobserver agreement Características anatômicas e funcionais do assoalho pélvico em nulíparas avaliadas por ultrassonografia tridimensional endovaginal: estudo caso-controle e avaliação da confiabilidade interobservador - Sthela Maria Murad-Regadas; Leonardo Robson Pinheiro Sobreira Bezerra; Claudio Regis Sampaio Silveira; Jacyara de Jesus Rosa Pereira; Graziela Olivia da Silva Fernandes; José Ananias Vasconcelos Neto; Iris Daiana Dealcanfreitas (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To determine anatomical and functional pelvic floor measurements performed with three-dimensional (3-D) endovaginal ultrasonography in asymptomatic nulliparous women without dysfunctions detected in previous dynamic 3-D anorectal ultrasonography (echo defecography) and to demonstrate the interobserver reliability of these measurements. METHODS: Asymptomatic nulliparous volunteers were submitted to echo defecography to identify dynamic dysfunctions, including anatomical (rectocele, intussusceptions, entero/sigmoidocele and perineal descent) and functional changes (non-relaxation or paradoxical contraction of the puborectalis muscle) in the posterior compartment and assessed with regard to the biometric index of levator hiatus, pubovisceral muscle thickness, urethral length, anorectal angle, anorectal junction position and bladder neck position with the 3-D endovaginal ultrasonography. All measurements were compared at rest and during the Valsalva maneuver, and perineal and bladder neck descent was determined. The level of interobserver agreement was evaluated for all measurements. RESULTS: A total of 34 volunteers were assessed by echo defecography and by 3-D endovaginal ultrasonography. Out of these, 20 subjects met the inclusion criteria. The 14 excluded subjects were found to have posterior dynamic dysfunctions. During the Valsalva maneuver, the hiatal area was significantly larger, the urethra was significantly shorter and the anorectal angle was greater. Measurements at rest and during the Valsalva maneuver differed significantly with regard to anorectal junction and bladder neck position. The mean values for normal perineal descent and bladder neck descent were 0.6 cm and 0.5 cm above the symphysis pubis, respectively. The intraclass correlation coefficient ranged from 0.62-0.93. CONCLUSIONS: Functional biometric indexes, normal perineal descent and bladder neck descent values were determined for young asymptomatic nulliparous women with the 3-D endovaginal ultrasonography. The method was found to be reliable to measure pelvic floor structures at rest and during Valsalva, and might therefore be suitable for identifying dysfunctions in symptomatic patients. OBJETIVO: Avaliar as medidas anatômicas e funcionais do assoalho pélvico utilizando a ultrassonografia tridimensional transvaginal em nulíparas assintomáticas sem disfunções do compartimento posterior evidenciado pela ecodefecografia. Demonstrar o grau de concordância entre observadores do método utilizado para medir as estruturas anatômicas. MÉTODOS: Voluntárias nulíparas assintomáticas foram submetidas à ecodefecografia para identificar alterações dinâmicas no compartimento posterior, incluindo aquelas anatômicas (retocele, intussuscepção, entero/sigmoidocele e descenso perineal) e funcionais (ausência de relaxamento ou contração paradoxal do puborretal) e avaliadas com ultrassonografia tridimensional transvaginal para determinar índices biométricos do hiato dos elevadores do ânus, espessura do músculo pubovisceral, comprimento da uretra, ângulo anorretal, posição da junção anorretal e posição do colo vesical. Todas as medidas foram comparadas em repouso e durante Valsalva; e determinado descenso perineal e do colo da bexiga. A variabilidade interobservador foi avaliada utilizando o coeficiente de correlação intraclasse. RESULTADOS: Foram avaliadas 34 voluntárias com a ecodefecografia e a ultrassonografia tridimensional transvaginal. Dessas, 20 foram incluídas no estudo. As 14 excluídas apresentavam alterações dinâmicas no compartimento posterior. Durante a manobra de Valsalva, a área hiatal foi significativamente maior. A uretra foi significantemente mais curta e o ângulo anorretal foi maior. Medidas em repouso e durante a Valsalva diferiram significativamente em relação à posição da junção anorretal e do colo vesical. A média de valor do descenso perineal e do descenso da bexiga foram de 0,6 cm e 0,5 cm acima da sínfise púbica, respectivamente. O coeficiente de correlação intraclasse variou entre 0,62-0,93. CONCLUSÕES: Foram determinados valores normais para os índices biométricos funcionais, descida perineal e colo vesical em nulíparas assintomáticas utilizando-se a ultrassonografia transvaginal tridimensional. É um método seguro para mensurar a anatomia do assoalho pélvico durante o repouso e a manobra de Valsalva, e pode ser adequado para a identificação de disfunções em pacientes sintomáticos.